Pemberdayaan Masyarakat Menggunakan Teknologi Probio_Fm dalam Pengolahan Pakan Ternak Ayam Merawang di Desa Pagarawan, Bangka Belitung - rufti puji astuti; Sujadmi Sujadmi; Novyandra Ilham Bahtera; Gusva Yetti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
This community service aimed utilizing probio_Fm technology in feed processing and animal health management for empower society. There were three steps in the activity they were socialization, demonstration, and monitoring and evaluation. Qualitative descriptive analysis was applied to analyze the data. The activity found that the beneficiaries had been empowered to make the feed and apply the Ayam Merawang health management by using Probio_Fm technology. The empowerment activity affected the increased knowledge of beneficiaries on the various source of feed material. There was some feed source used in the practice of fermented complete feed which was bran, corn, coconut pulp, rough fish, premix, pellets, molasses, and probiotics of probio_Fm. The feed smelled fermented and was tanned, testable, and durable feed. The durability of the feed could be up to 14 days. The application of probio_Fm technology through animal feed and water affected the increase of animal health, the reduction of bad smell of animal waste, the effective feed and animal health management by feed processing once time a week, and the low cost of feed which was Rp 5,000/1 kg with protein until 29% in 100 kg of feed. The utilization of the various potential source of materials animal feed in Merawang could be optimized by implementing the sustainable Probio_Fm technology.